Influence of Sex on Meat and Fat Quality from Heavy Alentejano Pigs Finished Outdoors on Commercial and High Fiber Diets - Martins, José Manuel (2023)
This work aimed to examine the effects of sex on meat and fat quality traits from thirty Portuguese Alentejano (AL) pigs reared in outdoor conditions. These pigs were divided into three groups and fed ad libitum. From ~40 to 130 kg LW, castrated (C group) and intact animals (I and IExp) consumed commercial diets. Until slaughter (~160 kg), C and I pigs remained on commercial diets, and IExp changed to a more sustainable experimental diet with locally produced pulses and byproducts. Samples were collected from the Longissimus lumborum (LL), Psoas major (PM), and dorsal subcutaneous fat (DSF). At ~160 kg, the PM muscle of intact pigs presented lower intra-muscular fat content than that of C pigs, while total collagen was higher. Additionally, PM myoglobin was lower and lightness (L*) was higher in intact pigs. Regarding DSF, moisture and total protein contents were higher and total lipids were lower in intact than in castrated pigs, while color parameters were not significantly different. Finally, antioxidant capacity measured in the LL muscle showed an overall lower value in intact pigs. However, lipid oxidation values were not significantly different between the experimental groups and only increased with storage time. Outdoor-reared intact AL pigs produced leaner and less saturated pork and fat compared to castrated ones. Despite the lower antioxidant activity observed in the LL muscles of intact pigs, the lipid oxidative stability of cooked meat was not different among the experimental groups.